1,846^-1
362^-1
<span>83,734^-1</span>
Answer:
r = h + m
Step-by-step explanation:
h = r - m
Switch sides.
r - m = h
Add m to both sides.
r - m + m = h + m
Simplify the left side. -m + m = 0
r = h + m
Answer:
-3 or decreasing by 3
Step-by-step explanation:
To find the average change, you only care about the first and last point which would be (3,17) and (8,2)
the overall change during that time is 2-17=-15 (for the f(x) side )
the overall change during that time is 8-3=5(for the x side)
all we have to do is -15/5=-3
therefore the average rate of change is -3
Answer:
2k
Step-by-step explanation:
Add:
-k + 3k
or
-1k + 3k
2k
(You have to add -1 + 3)
Hope this helps :)
Answer:
m = -12 / 6 = -2 / 1 = -2
So its -2